Short-term exposure to PM2.5 constituents and mortality risks for diabetes subtypes and related complications in eastern China - Jingjing Zhang; Jiaying Fang; Jiajun Shen; Yalin Zhang; Yunquan Zhang; Hao Zheng (Environment International)
Background: Although fine particulate matter (PM2.5) pollution is widely linked with diabetes-related morbidity and mortality, research on the short-term effects of its components across diabetes subtypes and complications is limited. Methods: We conducted an individual-level time-stratified case-crossover study by investigating over 55 thousand diabetes-related deaths in Jiangsu province of eastern China, between 2016 and 2019. Daily concentrations of total PM2.5 and its five primary components, including black carbon (BC), organic matter (OM), nitrate (NO3−), sulfate (SO42−), and ammonium (NH4+) were assigned to each death on case and control days at the residential address. Using conditional logistic regression and weighted quantile sum regression models, we assessed the associations between single and combined exposures to PM2.5 components and mortality from overall diabetes, its subtypes, and complications. Population fractions of diabetes deaths attributable to PM2.5 and its constituents were estimated using counterfactual analyses. Results: Each interquartile range (IQR) increase in the 2-day (the current and prior day) moving average of PM2.5 components was consistently associated with an elevated risk of overall diabetes mortality. The highest odds ratio (OR) per IQR increase was 1.033 (95 % confidence interval: 1.018, 1.049) for NO3− (IQR: 10.8 μg/m3), followed by 1.030 (1.015, 1.045) for NH4+ (IQR: 6.4 μg/m3), 1.027 (1.014, 1.040) for OM (IQR: 7.5 μg/m3), 1.025 (1.012, 1.038) for BC (IQR: 1.3 μg/m3), and 1.020 (1.006, 1.034) for SO42− (IQR: 6.3 μg/m3). Parallel associations with various PM2.5 components were only observed for type 2 diabetes (T2D) instead of type 1 diabetes. Among all diabetic complications, only diabetic nephropathy showed a notable nexus with PM2.5 mass and its constituents. Natural cubic smoothing analyses exhibited nearly linear, threshold-free concentration–response relationships between cause-specific diabetes-related mortality risk and PM2.5 components. For an IQR-equivalent increase in joint exposure, the estimated mortality ORs were 1.061 (1.033, 1.091) for overall diabetes, 1.065 (1.034, 1.097) for T2D, and 1.076 (1.011, 1.146) for diabetic nephropathy, respectively. Among PM2.5 constituents, NO3− and OM showed the highest estimated weights in the joint exposure model, accounting for over 70 % of the combined effect on diabetes-related mortality. We estimated that 1.55 % (0.45 %, 2.64 %) to 5.44 % (2.99 %, 7.90 %) of overall diabetes-related fatalities could be attributable to exposure to PM2.5 constituents. Conclusions: Our findings highlight the heightened mortality risks of T2D and diabetic nephropathy associated with short-term exposure to PM2.5 constituents. Our findings can aid environmental health policymakers in developing air quality standards for PM2.5 constituents and mitigating PM2.5-related loss of life among diabetic patients in China.